'Free, Bold, Joyous': The Love of Seaweed in Margaret Gatty and Other Mid-Victorian Writers. (1st February 2005) - Hunt, Stephen E.
Abstract : With particular reference to Gatty's British Sea-Weeds and Eliot's 'Recollections of Ilfracombe', this article takes an ecocritical approach to popular writings about seaweed, thus illustrating the broader perception of the natural world in mid-Victorian literature. This is a discursive exploration of the way that the enthusiasm for seaweed reveals prevailing ideas about propriety, philanthropy and natural theology during the Victorian era, incorporating social history, gender issues and natural history in an interdisciplinary manner. Although unchaperoned wandering upon remote shorelines remained a questionable activity for women, 'seaweeding' made for a direct aesthetic engagement with the specificity of place in a way that conforms to Barbara Gates's notion of the 'Victorian female sublime'. Furthermore, while women's contributions often received an uneven reception within the masculine institutions of professional science, marine botany proved to be a more accommodating area for participation. At Ilfracombe, Eliot wrote that she believed collecting and naming was a means to achieve distinct and definite ideas in her understanding of the world. The argument is developed that many needed to reorient their personal cosmologies in order to make sense of, and impose meaning upon, an uncertain world, thus contributing to the great debate about evolution.